RING Finger Protein 38 Is a Neuronal Protein in the Brain of Nile Tilapia, Oreochromis niloticus - Kai Lin Cham; Tomoko Soga; Ishwar S. Parhar (Frontiers Media S.A., 2017)
Really interesting new gene (RING) finger protein is a type of zinc-binding motif found in a large family of functionally distinct proteins. RING finger proteins are involved in diverse cellular processes including apoptosis, DNA repair, cell cycle, signal transduction, tumour suppressor, vesicular transport, and peroxisomal biogenesis. RING finger protein 38 (RNF38) is a member of the family whose functions remain unknown. To gain insight into the putative effects of RNF38 in the central nervous system, we localised its expression. The aim of this study was to identify the neuroanatomical location(s) of rnf38 mRNA and its peptide, determine the type of RNF38-expressing cells, and measure rnf38 gene expression in the brain of male tilapia. The distributions of rnf38 mRNA and its peptide were visualised using in situ hybridisation with digoxigenin-labelled RNA antisense and immunocytochemistry, respectively. Both were identically distributed throughout the brain, including the telencephalon, preoptic area, optic tectum, hypothalamus, cerebellum, and the hindbrain. Double-labelling immunocytochemistry for RNF38 and the neuronal marker HuC/D showed that most but not all RNF38 protein was expressed in neuronal nuclei. Quantitative real-time polymerase chain reaction showed the highest level of rnf38 mRNA in the midbrain, followed by the preoptic area, cerebellum, optic tectum, telencephalon, hindbrain and hypothalamus. These findings reveal a differential spatial pattern of RNF38 in the tilapia brain, suggesting that it has potentially diverse functions related to neuronal activity.